K.S.U aerobic swine-waste handling system (6 years of problems and progress) - B A Koch; G L Allee; R I Lipper; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
The Kansas State University Swine research Unit's aerobic-oxidation waste disposal system is functioning satisfactorily with minimum maintenance and supervision. Labor requirements are low. Odor is no problem. Waste fluid can be spread on the fields any time without creating a "public nuisance." Pigs are performing satisfactorily in the unit. Flies are easily controlled and suitable sanitation is easily maintained.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Swine-waste handling system; Fly control